Indonesia Indonesia - Maria Refyo Agnawenan Angwarmase; Eriana Dawai; Syafirah Alawiyah; Najwa Jawas (eCo-Fin, 2025)
The study aims to look into how financial responsibility and internal control systems affect how well the Peace of Christ Church does its job.  In order to provide effective and efficient services to its community, the church, which is a non-profit group, must handle its money in a clear and accountable way.  The poll method is part of a quantitative approach used in this study.  The data were gathered by sending surveys to 43 busy church members who were interested in events.  With the help of the most recent version of SPSS software, multiple linear regression was used to analyse the data. The results indicate that, partially, the internal control system has a significant influence on service performance, while financial accountability does not show a significant impact. However, simultaneously, both independent variables contribute 75.3% to the variation in service performance. These findings highlight the crucial role of internal control systems in enhancing the church’s service effectiveness, whereas financial accountability functions more as a supporting element in good organizational governance. Therefore, the church should continue to strengthen its internal control structure to ensure optimal and sustainable service to its members.